#### Answer

$\frac{-y-4}{y+3}$

#### Work Step by Step

$\frac{y+2}{y+3}$-2
=$\frac{y+2}{y+3}$-2 ($\frac{y+3}{y+3}$)
=$\frac{y+2-2(y+3)}{y+3}$
=$\frac{y+2-2y-6}{y+3}$
=$\frac{y-2y+2-6}{y+3}$
=$\frac{-y-4}{y+3}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{-y-4}{y+3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.